Efecto del Calcio en el cultivo de Sandía (Citrullus lanatus) y su impacto en el rendimiento - Díaz Naranjo, José Daniel (2021)
Ecuador has favorable environmental conditions for the cultivation of an infinity of plant species that can be considered as vegetables, among which the watermelon stands out. This document refers to the effect of Calcium in the cultivation of Watermelon (Citrullus lanatus) and its impact on yield, since Ca activates and regulates cell division and elongation, influences cell compartmentalization related to the specialization of cellular organs; It is responsible for holding plant cell walls together in the form of calcium pectate. The conclusions determine that to improve the effects of nutrition on the development and ripening of fruits, calcium plays a decisive role in relation to quality and organoleptic qualities; calcium and magnesium are provided by irrigation water, helping to improve productivity; The choice of certified varieties that adapt to the climatic conditions of the area can obtain good yields with the application of calcium of 2.5 L / ha, which helped to improve the percentages of Brix degrees in the fruit and its quality and good sweetness of the fruit ; The calcium correction helps with the fixation of the cell wall stimulating the plant in the formation of fruits, avoiding the shedding of flowers and incorporating micro and macro nutrients in the watermelon crop helping with the deficiencies that the plant presents more in stages of formation and fruit set.